Histological Effect of Ultra Violet (UV) Light on the Testis of Albino Wistar Rats - Uwuigbe Mathew; Ohiwerei Wisdom Omogbai; Ogbe O Clementina; Ajanwachukwu Ogbonna Wilson; Obeagu E I (International Journal of Applied and Scientific Research, 2024)
UV light, or ultraviolet light, is a type of radiation that falls between the visible light and X-ray regions of the electromagnetic spectrum. It is a form of electromagnetic radiation emitted by the sun and artificial sources, such as tanning beds and UV lamps. It has a shorter wavelength than visible light, ranging from 100 to 400 nanometers (nm). It is categorized into three types based on their wavelengths: UVA, UVB, and UVC. The aim of this study is to evaluate the histopathological effect of uv light on the testis of male Wistar albino rats. A total of fifty (50) adult Albino Wistar rats of comparable sizes were used for this study. They were divided into four equal groups (A – E) with ten (10) rats each. Group A served as the control and the rats were given distilled water and feed only. In addition to feed and water, Groups B rats were kept under Uv light for 30mins, Group C rats were kept under Uv light for 1hour twice daily, Group D rats were kept under Uv light for 2 hours thrice daily and Group E were kept under Uv light for 4 hours thrice daily. The administration was given daily for 14 days (2 weeks) and the weights of both the test and control animals was monitored before and after administration of Uv light. After the administration, the rats were put under light chloroform anaesthesia and the stomach was obtained. ANOVA was used to analyze the results of the weight and differences was considered significant at p<0.05 level of confidence. All data was expressed in table as mean ± standard deviation (SD). From the results, it was observed that Group B showed mild adenofibroma, Group C exhibited denatured testicular cells, indicating severe damage. Group D had adenocarcinoma and fatty tissue, suggesting potential malignancy and Group E presented fatty tissue. In conclusion, the exposure of testis to uv light cause significant alterations in testis histology